2004
DOI: 10.1111/j.1365-2982.2004.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of upper and lower gastrointestinal tract symptoms with body mass index in an Australian cohort

Abstract: Food modulates gastrointestinal (GI) function and GI symptoms could alter food intake, but it is not established whether or not obese people experience more or less GI symptoms. We aimed at evaluating the association between body mass index (BMI) and specific GI symptoms in the community. Population-based random samples from Sydney, Australia (n = 777) completed a validated questionnaire. The association of each GI symptom with BMI (kg m(-2)) categories was assessed using logistic regression analysis adjusting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
77
3
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 41 publications
9
77
3
6
Order By: Relevance
“…Directly comparable data arising from the Australian population are scant; however, the prevalence of aspirin and NSAID use in our sample was similar to that reported in other Australian studies (52,53). Other factors known to be associated with risks of EAC, notably symptoms of reflux and BMI, were similarly prevalent in our control series to other studies in the Australian population (54,55). We therefore consider the likelihood of biased selection to be no greater than for previous studies.…”
Section: Discussionsupporting
confidence: 69%
“…Directly comparable data arising from the Australian population are scant; however, the prevalence of aspirin and NSAID use in our sample was similar to that reported in other Australian studies (52,53). Other factors known to be associated with risks of EAC, notably symptoms of reflux and BMI, were similarly prevalent in our control series to other studies in the Australian population (54,55). We therefore consider the likelihood of biased selection to be no greater than for previous studies.…”
Section: Discussionsupporting
confidence: 69%
“…21 In 2008, Pourhoseingholi et al conducted a cross-sectional study in Tehran province where 40% of FC patients were overweight and 20% were obese, indicating a clear association between obesity and FC; however Zhao et al, in 2011 found a negative correlation between high BMI and FC and few studies reported no significant relationship between BMI and FC. [22][23][24] In 2013, Farzaneh et al evaluated the effects of demographic factors, BMI, alcohol drinking and smoking habits in 153 IBS patients against 163 non-IBS patients at Taleghani Hospital Gastroenterology Clinic at Tehran. The authors found no association between BMI and IBS in males but a significant association was seen among BMI <25 and female gender.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has been shown to be a determinant of acid reflux (24)(25)(26) and has also been linked with esophageal adenocarcinoma (13,27). In that context, our observation of modestly higher prevalence of obesity among Barrett's esophagus patients is perhaps not surprising.…”
Section: Discussionmentioning
confidence: 99%